THE ROLE OF SEXUAL PSYCHOEDUCATION IN FOSTERING SEXUAL AWARENESS AND SELF-DEFENSE SKILLS IN MADRASAH TSANAWIYAH STUDENTS - Mierrina Mierrina; Ummy Chairiyah; Nur Romdlon Maslahul Adi (Universitas Islam Negeri Mataram, 2024)
This research aims to determine the level of sexual knowledge and sexual awareness among students and assess the impact of the sexual awareness and self-defense program on madrasah tsanawiyah students. The researcher implemented a sexual awareness and self-defense program through sexual psychoeducation for madrasah tsanawiyah students. This research employs an experimental design known as the One Group Pre-test – Post-test Design. Data were collected through data collection instruments or scales measuring sexual knowledge and sexual awareness. The research findings the average scores of sexual knowledge and sexual awareness abilities showed an increase from pre-test to post-test. In the pre-test, the average score for these abilities was 13.33, whereas in the post-test, the abilities of students who had undergone the psychoeducational program on sexual awareness and self-defense improved to an average of 23.05. There is a noticeable mean difference that indicates improvement following the implementation of the sexual awareness and self-defense program. The Wilcoxon Signed Ranks Test conducted on the results yielded a z-value of 7.540 with a probability/significance level of 0.000 (p value ? 0.05).